Daire Eksenli Çubukların Dinamik Analizi - Çoban, Mehmet; Ayhan, Bahar; Kadıoğlu, Fethi (Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2008)
In this study, using Gâteaux differantial a functional is obtained for out-of-plane free vibrations of beam elements with rectangular cross sections. In dynamic analysis, the problem reduces to the solution of a standart eigenvalue problem and the mixed finite element is based upon a consistent mass matrix formulation. The circular beam element which have two nodes have been used. For circular beam, the element have one bending and one twisting moments, one shear force, two rotations and one displacement (2×6 DOF).

Bu çalışmada, Gâteaux türevi kullanılarak daire eksenli çubukların düzlem dışı serbest titreşimleri için fonksiyonel elde edilmiştir. Dinamik analizde problem, standart özdeğer problemine indirgenerek sıkıştırılmış kütle matrisi formülasyonunu esas alan karışık sonlu eleman yöntemi ile incelenmiştir. İki noda sahip dairesel çubuk eleman kullanılmıştır. Dairesel çubukta her eleman, bir eğilme ve bir burulma momenti, bir kesme kuvveti, iki dönme ve bir yerdeğiştirme olmak üzere (2×6) serbest derecesine sahiptir.

Conference Paper -- Theoretical and Applied Mechanical Turkish National Committee, 2008

Konferans Bildirisi -- Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2008